GHR/HindIII Locus Polymorphisms in Intron-2 GHR Gene of Papua Local Chicken - M. A. Mu'in; A. G. Murwanto (Jurnal Sain Peternakan Indonesia, 2021)
This study aimed to detect single nucleotide polymorphisms (SNPs) in intron-2 on growth hormone receptor (GHR) gene in Papua local chickens using the PCR-RFLP method to study its relationship with growth characteristics. Data on the bodyweight of 49 chickens aged 1, 2, 3, and 4 months (22 males, 27 females) and DNA samples were used for this study. The DNA fragment of size 718 bp in intron-2 of the GHR gene from the study chicken was successfully amplified using a pair of specific primers. The PCR-RFLP/HindIII analysis results found this locus's two genotypes (HindIII++ and HindIII--). HindIII+ and HindIII- alleles were 0.02 and 0.98, respectively.